Fund Flow of Financial Institutional Investors to Indian Stock Market: An Empirical Study. (June 2013) - Ananda, S.; Nair, Bibin
This study has tried to explore whether the foreign institutional investors (FIIs) have a significant impact on the Indian stock market, and also to find the linkages that these flows have with the exchange rate and the Index of Industrial Production. The study utilises data over a 13 year period (January 1995 to December 2007) for the variables from Centre for Monitoring Indian Economy (CMIE). The study found that FIIs net flow has a significant impact on the Indian stock market and is positively correlated with the Bombay Stock Exchange (BSE) Sensex movements though there is no evidence of causality between them. The study revealed the fact that the rupee–dollar exchange rates are negatively correlated with the FIIs flow. The Granger causality tests reveal that there is causation from FIIs flow to the rupee–dollar exchange rates but not vice versa. The study is divided into various sections. The first section gives an introduction to the study and the significance of the study. The second section presents a brief background to the study, including the determinants of FII flow, and literature review. The methodology is described in the third section, including the hypotheses and sampling. The results and findings of the research are discussed in the fourth section, while the last and fifth section comprises the conclusion to the study.